Pengaruh Kecanggihan Investor Dan Kualitas Auditor Terhadap Hubungan Antara Manajemen Laba Sebelum Initial Public Offering (IPO) Dengan Return Saham - Marfuah - (Universitas Islam Indonesia, 2012)
The main purpose of this research is to examine the availability profit management in scheme of iPO. In addition to this, the influence of the profit management on share return and also the influence of the sophistication of investor and the quality of auditor in the moderation of the relation between profit management before iPO and share return.Based on the selecteed samples, 38 companies which has undertake IPO during 1995-2008 and the examination of